Insights Into Causal Effects of Genetically Proxied Lipids and Lipid‐Modifying Drug Targets on Cardiometabolic Diseases - Liwan Fu; Qin Liu; Hong Cheng; Xiaoyuan Zhao; Jingfan Xiong; Jie Mi (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The differential impact of serum lipids and their targets for lipid modification on cardiometabolic disease risk is debated. This study used Mendelian randomization to investigate the causal relationships and underlying mechanisms. Methods Genetic variants related to lipid profiles and targets for lipid modification were sourced from the Global Lipids Genetics Consortium. Summary data for 10 cardiometabolic diseases were compiled from both discovery and replication data sets. Expression quantitative trait loci data from relevant tissues were employed to evaluate significant lipid‐modifying drug targets. Comprehensive analyses including colocalization, mediation, and bioinformatics were conducted to validate the results and investigate potential mediators and mechanisms. Results Significant causal associations were identified between lipids, lipid‐modifying drug targets, and various cardiometabolic diseases. Notably, genetic enhancement of LPL (lipoprotein lipase) was linked to reduced risks of myocardial infarction (odds ratio [OR]1, 0.65 [95% CI, 0.57–0.75], P1=2.60×10−9; OR2, 0.59 [95% CI, 0.49–0.72], P2=1.52×10−7), ischemic heart disease (OR1, 0.968 [95% CI, 0.962–0.975], P1=5.50×10−23; OR2, 0.64 [95% CI, 0.55–0.73], P2=1.72×10−10), and coronary heart disease (OR1, 0.980 [95% CI, 0.975–0.985], P1=3.63×10−14; OR2, 0.64 [95% CI, 0.54–0.75], P2=6.62×10−8) across 2 data sets. Moreover, significant Mendelian randomization and strong colocalization associations for the expression of LPL in blood and subcutaneous adipose tissue were linked with myocardial infarction (OR, 0.918 [95% CI, 0.872–0.967], P=1.24×10−3; PP.H4, 0.99) and coronary heart disease (OR, 0.991 [95% CI, 0.983–0.999], P=0.041; PP.H4=0.92). Glucose levels and blood pressure were identified as mediators in the total effect of LPL on cardiometabolic outcomes. Conclusions The study substantiates the causal role of lipids in specific cardiometabolic diseases, highlighting LPL as a potent drug target. The effects of LPL are suggested to be influenced by changes in glucose and blood pressure, providing insights into its mechanism of action.